Composición, estructura horizontal y diversidad de un bosque de terraza alta, distrito de San Pablo, Loreto, Perú. 2024 - Nuñez Rengifo, Kattia Isela (2025)
An analysis of the composition, horizontal structure and diversity of a high terrace forest was carried out in cutting plot 1 (PC 1) of the General Forest Management Plan (PGMF) for timber concessions No. 16-LOR-MAR/CON-MAD-2024-012, located in the district of San Pablo, Loreto. A total of 399 trees were recorded in plot 1, belonging to 36 species and 18 botanical families. The Myristicaceae family was the most numerous, with 72 specimens, representing 18.04% of the total. In plot 2, 317 trees were counted, distributed in 35 species and 18 botanical families. Here, the Fabaceae family leads with 68 trees, equivalent to 21.45%. The evaluation of the horizontal structure, using the importance value index (IVI), reveals that in both plots the most significant species from the ecological point of view is Virola flexuosa, with an IVI of 19.84% in plot 1 and 15.63% in plot 2, followed by Cedrelinga cateniformis, which has an IVI of 15.63% in plot 1 and 17.57% in plot 2. The Shannon-Wiener index values, which reach 4.82 in plot 1 and 4.84 in plot 2, reflect high diversity in both areas. Simpson's index for plot 1 is 0.2451, indicating moderate diversity, while plot 2 shows an index of 0.0287, indicating high diversity. Finally, the Margalef index, which is 5.84 in plot 1 and 5.90 in plot 2, also indicates high diversity in both cases. The hypothesis that there are variations in the composition, horizontal structure and diversity of the high terrace forest is confirmed.